تصميم نظام قطع جديد في قصاصة النباتات المحمولة - نوفل الأحمد; قيس إبراهيم (Tishreen University, 2017)
تم تصميم نظام قطع جديد لتحسين أداء وانتاجية قصّاصة النباتات المحمولة و لاستخدامها في البيئة القاسية ذات الحشائش القصبية و الكثيفة بكفاءة وجودة عاليين و بأدنى احتياجات للطاقة وفي قطع بعض المحاصيل التي تزرع في مساحات صغيرة. النظام الجديد يشمل ثلاثة أنماط: سلاسل بسيطة, سلاسل ذات شفرات مستقيمة وسلاسل بشفرات مائلة, كل سلسلة محمولة على قرص مركزي من الألمنيوم. تم اختبار السلاسل على الشّد, وكانت النتائج مرضية. اختُبرَت الأسلحة حقلياً على أربعة أنواع من السوق النباتية القمح, الذرة الصفراء حشيشة الفرس و الحلفا. قوة القص, الانتاجية, معدل استهلاك الوقود, و احتياجات الطاقة تم تحديدها وعند سرعات مختلفة للدوران, كانت السلاسل ذات الشفرات المستقيمة الأفضل في جودة القطع و أقل احتياجاً للطاقة عند قطع كل من الذرة الصفراء و حشيشة الفرس, كانت السلاسل ذات الشفرات المائلة أفضل بالنسبة لكل من القمح و الحلفا, كانت احتياجات الطاقة وقوى القطع أكبر ما يمكن عند استخدام السلاسل البسيطة. بشكل عام وجد إنه يمكن استخدام هذه الأسلحة بقصاصة النباتات المحمولة وبكفاءة أعلى من التصاميم القديمة. A new system was designed in portable plants-eater to improve the performance and productivity and for using it in the harsh environment containing like-cane dense brushes with high efficiency, quality and lowest power requirement and to harvest some crops are grown in small areas. The new system includes three types: link chain, straight blades chain and oblique blades chain, each chain is fixed on central aluminum disk. the three chains were tested on tensile, the results were satisfactory. The cutters was tested in the field on four types of stalk Wheat, Yellow Maize, Sorghum Helpenese and imperata cylindrical. Cutting force, productivity, fuel consumption, power requirement was calculated with deferent rotation speeds. The straight blades chain has the best cutting quality and lowest energy requirement on maize and sorghum halepense, the oblique blades chain was better on wheat and imperata cylindrical. The greatest values of energy requirement and cutting forces appeared with link chain cutter-head. In general, these cutter-heads are useable in weed-eater with higher efficiency than the old designs.